Members’ segmentation, service quality and behabioral intentions: a case study of a professional football team - Biscaia, Rui Daniel Gaspar Neto (2014)
This study aims to identify segments of members in a professional football team, and to compare service quality perceptions and behavioral intentions among these segments. The members registered in the club’s database were invited to complete a survey including demographic questions, measures of consumer behavior, service quality, and behavioral intentions. The results from a sample of 6820 participants allowed the identification of three distinct segments, named as ‘Occasional’, ‘Die-hard’, and ‘Weekend Lovers’. Results also indicate that these three segments of members showed statistically significant differences regarding service quality perceptions and behavioral intentions. Managerial implications of these results are discussed and suggestions for future research are provided.